Integrated Analog-Digital Robotics Learning System to Improve Elementary Students Computational Thinking - Agung Kridoyono; Mochamad Sidqon; Anton Breva Yunanda; Istantyo Yuwono (Jurnal Buana Informatika, 2026)
This study explores the implementation of an integrated analog–digital robotics learning model to improve computational thinking skills among elementary school students. The learning activities were arranged progressively, starting from analog sensor-based robotics experiments and continuing to programmable digital robot control. A total of 30 fifth-grade students participated in a four-week intervention program involving hands-on robotics activities. Students’ computational thinking abilities were evaluated through four dimensions: decomposition, pattern recognition, abstraction, and algorithmic thinking. The findings revealed improvements in all assessed indicators. The average score increased from 61.3 on the pretest to 82.7 on the posttest, with a medium normalized gain (N-gain) of 0.55. Statistical analysis using a paired-sample t-test also showed a significant difference between pretest and posttest scores (p < 0.05). These results indicate that integrated robotics learning can provide meaningful support for developing computational thinking skills in primary education.   Penelitian ini mengeksplorasi penerapan model pembelajaran robotika analog-digital terpadu untuk meningkatkan kemampuan berpikir komputasi pada siswa sekolah dasar. Kegiatan pembelajaran disusun secara progresif, dimulai dari eksperimen robotika berbasis sensor analog dan dilanjutkan dengan pengendalian robot digital yang dapat diprogram. Sebanyak 30 siswa kelas lima berpartisipasi dalam program intervensi empat minggu yang melibatkan aktivitas robotika langsung. Kemampuan berpikir komputasi siswa dievaluasi melalui empat dimensi: dekomposisi, pengenalan pola, abstraksi, dan berpikir algoritmik. Temuan ini menunjukkan adanya perbaikan pada seluruh indikator yang dinilai. Nilai rata-rata meningkat dari 61,3 pada pretest menjadi 82,7 pada posttest, dengan gain ternormalisasi sedang (N-gain) sebesar 0,55. Analisis statistik menggunakan uji-t berpasangan juga menunjukkan perbedaan yang signifikan antara skor pretest dan posttest (p < 0,05). Hasil tersebut menunjukkan bahwa pembelajaran robotika terpadu dapat memberikan dukungan yang berarti bagi pengembangan keterampilan berpikir komputasi pada pendidikan dasar.